Frequency of diarrheogenic Escherichia coli isolated from children in a pediatric hospital in Lima-Perú - Roque A., Mirtha (2018)
Diarrhea continues to be a health problem worldwide, especially in developing countries where it is responsible for 1,87 million deaths / year in children under 5 years of age. In Peru it has been shown that diarrheogenic Escherichia coli are an important cause of diarrhea in children. The objective of this research was to determine the frequency of enteropathogenic Escherichia coli (EPEC) in children under 5 years of age in a pediatric hospital in Lima, Peru. A total of 70 diarrheic stool samples were collected from children with clinical symptoms of acute diarrhea at the Pediatric Emergency Hospital, during the months of June to December 2015. Isolation and biochemical identification was performed by co-cultures and conventional biochemical tests, the identification of enteropathogenic Escherichia coli (EPEC) was performed by serotyping using polyvalent and monovalent antisera to the O somatic antigens. The determination of the somatic antigen "O" was performed by the plate agglutination technique, following the procedure described by the antisera supplier PROBAC DO BRAZIL. We isolated 50 (71.4%) strains of diarrheic Escherichia coli of which 36 (72%) were of the enteropathogenic serotype (EPEC) being the most frequent serogroups O119 (22,2%), O158 (16,7%), O142 (11,1%), O127 (8,3%), O55 (19,4%), O86 (8,30%), O125 (13,9%), 14(28%) corresponded to the Shiga toxin producing serotype (STEC),the most frequent serogroup being O111(28%). 28,6% (20/70) did not show the presence of E.coli.